Testing unified growth theory: Technological progress and the child quantity-quality tradeoff - Jakob Brøchner Madsen; Holger Strulik (Quantitative Economics, 2023)
A core mechanism of unified growth theory is that accelerating technological progress induces mass education and, through interaction with child quantity-quality substitution, a decline in fertility. Using unique new data for 21 OECD countries over the period 1750-2000, we test, for the first time, the validity of this core mechanism of unified growth theory. We measure a country's technological progress as patents per capita, R&D intensity, and investment in machinery, equipment, and intellectual property products. While controlling for confounders, such as income growth, mortality, and the gender wage gap, we establish (1) a significant impact of technological progress on education (positive) and fertility (negative); (2) that accelerating technological progress stimulated the fertility transition; and (3) that the baseline results are supported in 2SLS regressions using genetic-distance weighted foreign patent-intensity, compulsory schooling years, and minimum working age as instruments.
Keywords: I25; J10; N30; O30; O40; 330; Technological progress; fertility; education; quantity-quality tradeoff; unified growth theory